2018
DOI: 10.4049/jimmunol.1701284
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Homozygous Variants in the STING-Encoding TMEM173 Gene in HIV Long-Term Nonprogressors

Abstract: Among HIV-infected individuals, long-term nonprogressor (LTNP) patients experience slow CD4 T cell decline and almost undetectable viral load for several years after primary acquisition of HIV. Type I IFN has been suggested to play a pathogenic role in HIV pathogenesis, and therefore diminished IFN responses may underlie the LTNP phenotype. In this study, we examined the presence and possible immunological role of multiple homozygous single-nucleotide polymorphisms in the stimulator of IFN genes (STING) encodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…In neither study were differences in R232H prevalence reported. Another study suggests that STING-HAQ homozygosity may result in slower disease progression in HIV-infected individuals (44). Systematic studies using mouse models such as the ones described in this manuscript could be useful in predicting clinical consequences of carrying these genetic variants.…”
Section: Discussionmentioning
confidence: 94%
“…In neither study were differences in R232H prevalence reported. Another study suggests that STING-HAQ homozygosity may result in slower disease progression in HIV-infected individuals (44). Systematic studies using mouse models such as the ones described in this manuscript could be useful in predicting clinical consequences of carrying these genetic variants.…”
Section: Discussionmentioning
confidence: 94%
“…Whole-exome sequencing was performed as previously described (Nissen et al, 2018). Variant call files (VCF) were filtered using the approach described in Supplementary Method 1.…”
Section: Methodsmentioning
confidence: 99%
“…Blood was collected in Lithium Heparin-stabilized tubes and isolated as previously described (Nissen et al, 2018). MdMs were differentiated from PBMCs as previously described (Jorgensen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…All protocols were approved and methods carried out were in accordance with relevant guidelines and regulations. Some of the HIV patients included here have also been described in another study 45 .…”
Section: Methodsmentioning
confidence: 99%